Development of scintillating calorimeters for the CRESST II experiment - Di Stefano P.; Bruckmayer M.; Cozzini C.; Frank T.; Hauff D.; Pergolesi D.; Probst F.; Seidel W.; Sergeev I.; Leo Stodolsky; Uchaykin (Uchaikin) S. V. Sergey Victorovich; Cooper S.; et al. (2001, 2001)
В фонде НТБ ТПУ отсутствует